Why rural communities in India delay seeking eye care - Nicholson, Maneck D.; Krishnan, Radhika; Rogye, Ashwini (International Journal Of Community Medicine And Public Health, 2025)
Background: The purpose of the study was to assess the willingness to use eye care services among individuals with self-reported visual difficulties in rural Maharashtra, and to identify demographic and psychosocial factors influencing service uptake. Methods: A cross-sectional survey was conducted among participants with visual complaints during rural outreach camps. Data on sociodemographic characteristics, duration of visual symptoms, and willingness to utilize various eye care services were collected. Logistic regression was used to evaluate associations between demographic variables and the desire to use each service. Results: While willingness to undergo an eye examination was high (91.6%), the uptake of treatment services was significantly lower: 67.4% for eyeglasses, 56.7% for medications, and 58.5% for surgery. Older age, longer symptom duration, and unemployment were negatively associated with willingness to use eyeglasses. Literacy and employment status showed no consistent link with willingness to accept surgery or medications. Notably, no demographic variable strongly predicted willingness for surgery, indicating that broader awareness and perception-related barriers are influential. Conclusion: Despite the availability of free services, a significant number of individuals with visual complaints remain hesitant to seek treatment particularly surgery and medications. These results underscore the importance of targeted educational efforts, community awareness programs, and trust-building initiatives to promote service utilization among underserved populations.